2016
DOI: 10.1155/2016/2432808
|View full text |Cite
|
Sign up to set email alerts
|

Mortality Related Risk Factors in High-Risk Pulmonary Embolism in the ICU

Abstract: Introduction. We sought to identify possible risk factors associated with mortality in patients with high-risk pulmonary embolism (PE) after intensive care unit (ICU) admission. Patients and Methods. PE patients, diagnosed with computer tomography pulmonary angiography, were included from two ICUs and were categorized into groups: group 1 high-risk patients and group 2 intermediate/low-risk patients. Results. Fifty-six patients were included. Of them, 41 (73.2%) were group 1 and 15 (26.7%) were group 2. When c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
16
1
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(23 citation statements)
references
References 27 publications
(48 reference statements)
5
16
1
1
Order By: Relevance
“…Our ndings are consistent with those of Cugno et al [41,42] and Agrawal et al [41,42]. The rate of thrombolytic therapy was high in our study compared with that reported in previous studies [43,44]. This difference may be explained by the low rate of conditions that contraindicate thrombolytic treatment, including cancer, surgery, and pregnancy in our study or by the high rate of high-risk patients in our cohort.…”
Section: Discussionsupporting
confidence: 93%
“…Our ndings are consistent with those of Cugno et al [41,42] and Agrawal et al [41,42]. The rate of thrombolytic therapy was high in our study compared with that reported in previous studies [43,44]. This difference may be explained by the low rate of conditions that contraindicate thrombolytic treatment, including cancer, surgery, and pregnancy in our study or by the high rate of high-risk patients in our cohort.…”
Section: Discussionsupporting
confidence: 93%
“…Our findings confirm that subjects in the ICU are at high risk for both DVT and PE, due to the high number of risk‐factors. Moreover, our study confirms the results of a few studies recently published, showing a high incidence of PE (ranging from 6 to 20%) in patients requiring ICU admission, despite prophylactic measures …”
Section: Discussionsupporting
confidence: 91%
“…Moreover, our study confirms the results of a few studies recently published, showing a high incidence of PE (ranging from 6 to 20%) in patients requiring ICU admission, despite prophylactic measures. [1][2][3][4][5]17,18 In addition, we have established-in the current studythat PE is associated with poor outcome. In fact, the development of this complication is associated with a high mortality rate, a high rate of nosocomial infections, and a prolonged ICU and in-hospital length of stay (LOS).…”
Section: Discussionmentioning
confidence: 59%
“…The mortality rate of acute massive pulmonary thromboembolism was about 30% [3][4] , which was very high 1,2 , particularly in patients with shock or heart failure,, so the risk of mortality should be assessed as early as possible to maintain more effective treatments [5][6][7] . The European Society of Cardiology has divided the prognostic risk into 3 levels.…”
Section: ■ Introductionmentioning
confidence: 99%